VIRTUAL REALITY DEVELOPMENT IN AN EFFORT TO IMPROVE THE READINESS OF OFFICE ADMINISTRATION EDUCATION STUDENTS TO FACE TEACHING SKILLS PRACTICE - Wulan Kartika Sari; Osly Usman; Susan Febriantina (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2024)
This research was conducted with the aim of determining the level of feasibility and practicality of Virtual Reality learning media in teaching and learning strategy courses on microteaching material. This research uses the Research and Development (RnD) method with the ADDIE (Analysis, Design, Implementation, Evaluation) development model. The research subjects consisted of 1 material expert and 1 media expert as well as 10 6th semester students of the Office Administration Education Study Program, Faculty of Economics, Universitas Negeri Jakarta. The data collection technique uses a questionnaire with a 1-5 Likert scale. Data analysis techniques were carried out using expert validation tests and practicality tests. Based on validation tests carried out by 1 material expert and 1 media expert, the average percentage result was 94.5%, which means the category was very feasible. Based on the results of practicality tests for small and large groups, an average percentage score of 95% was obtained in the very practical category. Therefore, the results of the research and development that have been carried out are declared very feasible and very practical and can be used in learning activities.